(untitled) (Bangladesh Journal of Medical Science, 2022)
Traumatic brain injury is one of the leading causes for cognitive-linguistic impairments in individuals. Considering cerebral lateralization, the type of communication impairments does depend on the hemisphere that is damaged. The current study reports about a 26-year-old female who has underwent right fronto-temporo-parietal (FTP) craniotomy and evacuation of acute subdural hematoma, followed by left FTP decompressive craniotomy and conservative evacuation of the left temporal contusion. A detailed assessment focussing on the linguistic, cognitive, and speech skills were done using formal and informal measures. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 422-425